The self-efficacy in patient-centeredness questionnaire – a new measure of medical student and physician confidence in exhibiting patient-centered behaviors. Issue 1 (December 2015) - Zachariae, Robert; O'Connor, Maja; Lassesen, Berit; Olesen, Martin; Kjær, Louise; Thygesen, Marianne; Mørcke, Anne
Abstract Background Patient-centered communication is a core competency in modern health care and associated with higher levels of patient satisfaction, improved patient health outcomes, and lower levels of burnout among physicians. The objective of the present study was to develop a questionnaire assessing medical student and physician self-efficacy in patient-centeredness (SEPCQ) and explore its psychometric properties. Methods A preliminary 88-item questionnaire (SEPCQ-88) was developed based on a review of the literature and medical student portfolios and completed by 448 medical students from Aarhus University. Exploratory Principal Component analysis resulted in a 27-item version (SEPCQ-27) with three underlying self-efficacy factors: 1) Exploring the patient perspective, 2) Sharing information and power, and 3) Dealing with communicative challenges. The SEPCQ-27 was completed by an independent sample of 291 medical students from 2 medical schools and 101 hospital physicians. Results Internal consistencies of total and subscales were acceptable for both students and physicians (Cronbach's alpha (range): 0.74–0.95). There were no overall indications of gender-related differential item function (DIF), and a Confirmatory Factor Analysis (CFA) indicated good fit (CFI = 0.98; NNFI = 0.98; RMSEA = 0.05; SRMR = 0.07). Responsiveness was indicated by increases in SEPCQ scores after a course in communication and peer-supervision (Cohen'sd (range): 0.21 to 0.73;p : 0.053 to 0.001). Furthermore, positive associations were found between increases in SEPCQ-scores and course-related motivation to learn (medical students) and between SEPCQ scores and years of clinical experience (physicians). Conclusions The final SEPCQ-27 showed satisfactory psychometric properties, and preliminary support was found for its construct validity, indicating that the SEPCQ-27 may be a valuable measure in future patient centered communication training and research.